Law Enforcement and Liability of Government Officials for Spatial Planning Violations at PIK-2 Area Tangerang Regency - Chadijah, Siti; Yusdiansyah, Efik; Jamilah, Lina (Jurnal Pembaharuan Hukum, 2025)
Determination Project National Strategic Area in the Pantai Indah Kapuk-2 (PIK-2) area, Tangerang Regency, has caused polemic Because suspicion spatial planning violations and lack of analysis impact environment as well as social for public around. Research This aim analyze policy determination of PIK-2 as Project National Strategic and enforcement justice in implementation regulations the method law normative used with reviewing secondary data in the form of regulation legislation and documents related. Findings main show that determination of PIK-2 not in accordance with Constitution Number 26 of 2007 concerning Spatial Planning and Banten Regional Regulation Number 1 of 2023. Regulatory process done without notice spatial planning regulations and impacts environment in a way comprehensive and minimal involvement community. Impact identified concrete covering damage environment coast and loss access public to land productive. Research propose giving sanctions in the form of enforcement law strict to the issuing official regulations No in accordance rules to avoid violations in the future. The implication is that enforcement more laws strong and evaluation repeat PIK-2 Project National Strategic policy is important done with involving community and stakeholders interests so that development walk sustainable, fair, and maintain sustainability environment as well as social.